2020
DOI: 10.3390/ijfs8030057
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Share Repurchase Programs in Vietnam: Completion Rates and Short-Term Returns

Abstract: Stock repurchases have become a preferred method of distributing cash to stockholders. However, given the high level of information asymmetry and weak corporate governance as well as poor investor protection in Vietnam, many Vietnamese firms use stock repurchases as a tool to manipulate stock prices in the market. Using event study methodology and Tobit regression models, this study examines the stock price behaviors surrounding the event dates and the impact of earnings management activities prior to the stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…There has been a considerable amount of literature on share repurchases in the past, covering a variety of motives, such as capital restructuring, dividend substitution, surplus cash flow, managing earnings per share (EPS), increasing shareholder wealth, and deterring takeovers. EPS improvements are a primary corporate driver of stock repurchases, according to Cao et al (2020), who found a positive correlation between earnings management strategies and stock repurchases in Vietnam. Jena et al (2019) found that promoter holdings and earnings quality are negatively correlated, and Indian companies engage in opportunistic earnings management before buybacks.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a considerable amount of literature on share repurchases in the past, covering a variety of motives, such as capital restructuring, dividend substitution, surplus cash flow, managing earnings per share (EPS), increasing shareholder wealth, and deterring takeovers. EPS improvements are a primary corporate driver of stock repurchases, according to Cao et al (2020), who found a positive correlation between earnings management strategies and stock repurchases in Vietnam. Jena et al (2019) found that promoter holdings and earnings quality are negatively correlated, and Indian companies engage in opportunistic earnings management before buybacks.…”
Section: Introductionmentioning
confidence: 99%